(3GdGbJUGO GdbjGSj fXQjI h Mdhd (B:s (3JWHjb HGSJNOGe HQfGeL (BMinitab ,Relase 14 /s - (3GdYPGQj, YOfGf OGhO eMeOs ((3YeGf(B: s (3OGQ LQjQ(B, s, 2010)
(3GdHjGfGJ h GdfeGPL (B: (3fehPL GdGfMOGQ GdHSjW , GdGfMOGQ GdeJYOO , GdJbOjQ HGSJOGe GdceHjhJQ, GdeTGcd GdbjGSjI (B: (3eTcdI GdJYOO GdNWj , GdQJHGW GdPGJj h eTcd YOe KHGJ JLGfS GdJHGjf , GdeJZjQGJ GdNGQLjI h GdOGNdjI GdeNJdaI RefG , JeGQjf GdfeGPL GdBfjI , GdJMjR GdBfj h eTcd GdJTNjU , WQb JbOjQ GdfeGPL GdBfjI (B.s
(3eQGLY U(B.189 (3; edGMb U(B191s
Keywords: (3GdEbJUGO GdQjGVjs; (3GdGbJUGO GdbjGSjs; (3GdJfHDs